Optimal excitation conditions for indistinguishable photons from quantum dots. (18th December 2015) - Huber, Tobias; Predojević, Ana; Föger, Daniel; Solomon, Glenn; Weihs, Gregor
Abstract: In this paper, we present a detailed, all optical study of the influence of different excitation schemes on the indistinguishability of single photons from a single InAs quantum dot. For this study, we measure the Hong–Ou–Mandel interference of consecutive photons from the spontaneous emission of an InAs quantum dot state under various excitation schemes and different excitation conditions and give a comparison.